Assessing Biological Response to Bevacizumab Using 18F-Fluoromisonidazole PET/MR Imaging in a Patient with Recurrent Anaplastic Astrocytoma. (22nd February 2015) - Barajas, Ramon F.; Pampaloni, Miguel H.; Clarke, Jennifer L.; Seo, Youngho; Savic, Dragana; Hawkins, Randall A.; Behr, Spencer C.; Chang, Susan M.; Berger, Mitchel; Dillon, William P.; Cha, Soonmee
Abstract : We present our initial experience in using single modality fluoromisonidazole (FMISO) PET/MR imaging to noninvasively evaluate the biological effects induced by bevacizumab therapy in a patient treated for recurrent high grade glioma. In this index patient, bevacizumab therapy resulted in the development of nonenhancing tumor characterized by reduced diffusion and markedly decreased FMISO uptake in the setting of maintained CBF and CBV. These observations suggest that the dynamic biological interplay between tissue hypoxia and vascular normalization occurring within treated recurrent high grade glioma can be captured utilizing FMISO PET/MR imaging.